Formação em serviço social em tempos de pandemia : os direcionamentos das entidades representativas do serviço social em relação à implementação do ensino remoto emergencial - Corrêa, Edjane da Silva Barbosa (2023)
The directions adopted by the entities representing the Social Service, Federal Council of Social Service-CFESS, Regional Council of Social Service-CRESS, Brazilian Association of Teaching and Research in Social Service-ABEPSS and National Executive of Social Service Students-ENESSO for the adoption of Emergency Remote Teaching-ERE in training in Social Service is the theme of this dissertation and its objective is to: Analyze the directions of Social Service representative entities in relation to distance learning-EaD and the implementation of ERE, which unfolded into the following specific objectives: to investigate the implementation of EAD in Brazil and the commodification higher education; revive the discussion of distance learning in Social Services; Identify the documentation prepared and published by the Service's, Representative entities regarding emergency remote teaching and identify the guidelines adopted by the Service's representative entities for implementing emergency remote teaching within Social Service courses. The research will developed based on documentary and bibliographic analysis with a qualitative approach. It is an exploratory study and results in the representative entities of Social Service reaffirming the defense of face-to-face training and reinforcing the discourse on the incompatibility of distance learning for training. Therefore, it maintains the positioning as ERE. Regarding the guidelines for adopting the ERE, the entities: CFESS, CRESS, ABEPSS, and ENESSO published documents calling on the professional category to debate the ERE. From this debate, it revealed that the experience of adopting ERE demonstrates the trends of permanence with the use of ICTs that will continue to adopted as teaching strategies. The major challenge of the category in Social Work training is maintaining the quality of teaching, challenges that show that the ERE teaching model has led to fragmentation in the quality of teaching, mainly the trivialization of supervised internships.